CASE STUDY OF PANLEUKOPENIA IN A CAT AT JAKARTA ANIMAL CLINIC - Fauziah Muthia Rahmah; Tetty Barunawati Siagian (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Cats are carnivorous mammals that are susceptible to various infectious diseases, one of which is feline panleukopenia. Feline panleukopenia virus (FPV) infection is caused by a member of the Parvoviridae family, a non-enveloped, single-stranded DNA virus with a single antigenic serotype. This case report aimed to detect FPV infection in a cat using a rapid antigen test and hematological analysis. A male Maine Coon cat named Susu, weighing 5.1 kg, was presented to a veterinary clinic on November 5, 2025, for a routine health examination. According to the owner, the cat had not received deworming treatment for approximately one year. Physical examination revealed a body temperature of 39.3°C and an overall normal clinical condition. No abnormalities were observed in the respiratory system or oral cavity. However, the feces were slightly loose, and tapeworm segments were detected. Further testing using a rapid FPV antigen test yielded a positive result. Despite this finding, the cat did not exhibit the typical clinical signs of feline panleukopenia, such as lethargy, vomiting, or severe diarrhea. This discrepancy may indicate a subclinical infection, an early stage of disease, or a false-positive rapid test result. Therefore, additional diagnostic testing, such as polymerase chain reaction (PCR), is recommended to confirm the diagnosis. Case management consisted of supportive and symptomatic treatment, along with therapy targeting the parasitic infection. Improved hygiene measures and close monitoring were also recommended to minimize the risk of disease progression and transmission.